Blood Brothers: The Criminal Underworld of Asia - Lintner, B. (Palgrave Macmillan US, 2003)
Cover -- Half-Title -- Title -- Copyright -- Contents -- A note on names -- Acknowledgements -- Introduction -- 1 Whore of the East -- 2 The City of the Name of God -- 3 The dark masters of Kabuki -- 4 A country without limits -- 5 The Great Golden Peninsula -- 6 The pirate republic -- 7 Wizardry in the land of Oz -- 8 Climbing the mountain of gold -- Appendix: The 36 Oaths of China's Triad Societies -- Notes -- Bibliography -- Index.